Analisa Total Productive Maintenance Guna Meningkatkan Produktivitas Mesin Ekstrusi Type 2500 Menggunakan Metode Overall Equipment Effectiveness (OEE) - Muhazir, Achmad; Sinaga, Zulkani; Pratama, Gusti Andhika Aji (Journal of Industrial and Engineering System, 2022)
Manufacturing industry companies are always faced with productivity, quality and delivery problems as demanded from customers, PT. XYZ is engaged in manufacturing various aluminum profile products during the 2020 period, the company experienced a type 2500 extrusion machine downtime of 9807 minutes, exceeding the company's standard of 7800 minutes a year, this is one of the causes of a decline in production. This study aims to determine the effectiveness of the machine using the OEE (overall equipment effectiveness) method, to increase the productivity of the type 2500 extrusion machine from the results of the six big losses analysis to identify the main cause of the downtime of the type 2500 extrusion machine. The results show that the overall equipment effectiveness measurement is obtained the average Avaibility Ratio presentation is 92.24%, Performance Ratio is 49.56% and Quality Rate is 99.72% so that the average overall equipment effectiveness value is 45.61% where this value is still below the average ideal value overall equipment effectiveness is 85%. The results of the measurement of six big losses obtained the results of downtime values: equipment failure losses 3.81%, setup and adjustment losses 3.95%, speed losses: idle and minor stoppage 3.03%, reduce speed losses 46.51%, quality losses: defect losses 0.13%, reduced yield 0% , from these data it is known that the main problem is in the speed losses section with the highest loss in reduce speed losses of 46.51%. The factors that dominate the main cause of downtime for the 2500 extrusion machine are log heater, puller, dummi block, loader, finish cut saw, stem, and table.